Magnesium as an intrinsic component of human otoconia - Walther, Leif Erik (Acta oto-laryngologica, 2018)
OBJECTIVES: To investigate morphology changes of artificial otoconia (CGC) in the presence of magnesium during growth under in vitro conditions. - METHODS: Investigating human otoconia by environmental scanning electron microscope and determining their magnesium content by energy-dispersive X-ray microanalysis (EDX). Comparing structural and morphological data of human and artificial otoconia (CGC, Ca1Mg0) without and with magnesium substitution (Ca1-xMgx). - RESULTS: EDX- and X-ray data reveals that the inorganic component in human otoconia consists of calcite containing a minor amount of magnesium substitution (Ca1-xMgx). CGC containing magnesium (length 397.0 ± 146.4 µm, diameter 325.6 ± 100.1 µm) are slimmer and significantly smaller (p < .01) than pure CGC (length 548.6 ± 160 µm, diameter 373.0 ± 110.4 µm) and reveal a significant influence on the final morphology. The length/diameter ratio is significantly higher by incorporation of magnesium into CGC (1.84 ± 0.25 µm versus 1.48 ± 0.11 µm in pure CGC, p < .01), which brings the overall shape to a close relationship with human otoconia (1.98 ± 0.08 µm). - CONCLUSIONS: Magnesium is an intrinsic component of human otoconia by partial substitution of calcium in the calcite crystal structure (Ca1-xMgx) and affects the development of the shape of artificial otoconia (calcite gelatin composites, CGC).